Pelatihan Pemanfaatan Aplikasi Quizalize dalam Pembelajaran Siswa di MAN 2 Sinjai - Nurjannah Nurjannah; Nurfadhilah Nurfadhilah; Nurfiana Nurfiana; Danial Danial (LSM Catimore dan Sahabat, 2023)
This service aims to provide training to teachers, especially teachers at MAN 2 Sinjai in utilizing the Quizalize application learning media. This is motivated by the rapid development of technology, so that teachers are required to utilize learning media in conveying subject matter. Based on the facts in the field, teachers have less interest and ability to utilize technology-based learning media. Therefore, this training focuses on the use of learning media that are attractive to teachers and can be used to deliver innovative learning materials. The method used in this training is a presentation method related to the use of the Quizalize application and dialogic discussions with the teacher. The material presented in this training included an introduction to Quizalize features as an interactive learning medium, and the steps for creating a teacher account in this application. After this activity was carried out, the results were obtained, namely, increasing teacher understanding, competence, and creativity in utilizing technology-based learning media.